2018
DOI: 10.1111/hir.12214
|View full text |Cite
|
Sign up to set email alerts
|

Identification and description of controlled clinical trials in Spanish language dental journals

Abstract: References to the identified CCTs are now available in CENTRAL, the Cochrane Collaboration repository for these studies. We call for adherence to the CONSORT statement in dentistry to improve reporting of CCTs in journals published in Spanish language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…This pattern seemed to increase over time, as half of all eligible RCTs over the last 8 years ( n = 80; 50.3%) were published in journals edited in English. A plausible hypothesis may be that journals in English are likely to have a higher impact factor and broader readership (Villanueva et al, 2018) and therefore, more attractive to local authors (Loezar et al, 2018; Villanueva et al, 2018). Our study incorporated only electronic searches in literature databases where journals are indexed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern seemed to increase over time, as half of all eligible RCTs over the last 8 years ( n = 80; 50.3%) were published in journals edited in English. A plausible hypothesis may be that journals in English are likely to have a higher impact factor and broader readership (Villanueva et al, 2018) and therefore, more attractive to local authors (Loezar et al, 2018; Villanueva et al, 2018). Our study incorporated only electronic searches in literature databases where journals are indexed.…”
Section: Discussionmentioning
confidence: 99%
“…This would retrieve further RCTs published by Spanish research teams regardless of the indexing status of the publishing journal. The Iberoamerican Cochrane Centre has carried out similar projects to date; the identified RCTs were submitted to CENTRAL, the Cochrane Collaboration's controlled trials database (Arevalo‐Rodriguez et al, 2018; Gutarra‐Vilchez et al, 2016; Loezar et al, 2018; Martí et al, 1999; Sanclemente et al, 2015; Turrillas et al, 2017; Villanueva et al, 2018) As a result, RCTs published in non‐indexed journals have been given greater visibility (Pardo‐Hernandez et al, 2017). In our study, the newly identified RCTs not included in CENTRAL were submitted to this database through the Cochrane Register of Studies (CRS), which works as a data management tool and a data repository.…”
Section: Discussionmentioning
confidence: 99%
“…We will update these studies by hand searching the most recently published issues of the journals included in these studies. The methods for handsearching are published elsewhere (21,(24)(25)(26)(27). We will also search for new journals in these medical fields that could have emerged after 2015, following a previously published methodology.…”
Section: Data Sourcementioning
confidence: 99%
“…Being able to identify evidence to inform practice was the focus of Villanueva et al. 's () study to identify controlled clinical trials in Spanish‐language dentistry journals with the aim of providing access to this body of evidence in a single source. A total of 17 051 articles in 107 journals were hand‐searched identifying 244 controlled clinical trials.…”
Section: In This Issue…mentioning
confidence: 99%